Loss of HER2 Positivity after Trastuzumab in HER2-Positive Gastric Cancer: Is Change in HER2 Status Significantly Frequent?. (29th March 2015) - Ishimine, Yu; Goto, Akira; Watanabe, Yoshito; Yajima, Hidetaka; Nakagaki, Suguru; Yabana, Takashi; Adachi, Takeya; Kondo, Yoshihiro; Kasai, Kiyoshi
Abstract : Trastuzumab has recently been introduced as a treatment for HER2-positive metastatic and/or unresectable gastric cancer (MUGC); however, compared with breast cancer, some issues concerning HER2 and trastuzumab therapy for gastric cancer remain unclear. A 74-year-old woman received trastuzumab-containing chemotherapy for HER2-positive MUGC. She had a marked response to 8 months of chemotherapy, and gastrectomy and hepatic metastasectomy with curative intent were performed. The resected specimen showed complete loss of HER2 positivity in the residual tumor. For MUGC, a change in HER2 status during the course of the disease with or without chemotherapy has rarely been reported. However, in breast cancer, a significant frequency of change in HER2 status during the course of disease has been reported, and reevaluation of HER2 positivity in metastatic/recurrent sites is recommended. The choice of trastuzumab for MUGC is currently based on the HER2 status of the primary tumor at the time of initial diagnosis, without reassessment of HER2 status during the course of disease and/or in metastatic/recurrent sites, on the assumption that HER2 status is stable. However, our case casts doubt on the stability of HER2 in gastric cancer.